Syringomyelia and arachnoiditis. Issue 2 (February 1990) - Caplan, L R; Norohna, A B; Amico, L L
Abstract : Five patients with chronic arachnoiditis and syringomyelia were studied. Three patients had early life meningitis and developed symptoms of syringomyelia eight, 21, and 23 years after the acute infection. One patient had a spinal dural thoracic AVM and developed a thoracic syrinx 11 years after spinal subarachnoid haemorrhage and five years after surgery on the AVM. A fifth patient had tuberculous meningitis with transient spinal cord dysfunction followed by development of a lumbar syrinx seven years later. Arachnoiditis can cause syrinx formation by obliterating the spinal vasculature causing ischaemia. Small cystic regions of myelomalacia coalesce to form cavities. In other patients, central cord ischaemia mimics syringomyelia but no cavitation is present. Scar formation with spinal block leads to altered dynamics of cerebrospinal fluid (CSF) flow and contributes to the formation of spinal cord cystic cavities.